The Role of m-Learning in Project-Based Learning Models in Elementary Schools - Mamuaja, Marlin Penina; Rawis, Joulanda A.M.; Lengkong , Jeffry Sony Junus; Rotty, Viktory Nicodemus Joufree (International Journal of Information Technology and Education, 2023)
Project-based education has become an increasingly popular approach in today's education system, especially at the primary school level. Project-based learning allows students to engage in real activities that involve exploring, collaborating, and applying the concepts they learn in real-life contexts. In the digital era that continues to grow, m-Learning (learning via mobile devices) has become an important instrument in helping educators implement project-based learning models in elementary schools. This study aims to investigate the role of m-Learning in a project-based learning model in elementary schools. This study will involve collecting qualitative and quantitative data through classroom observations, teacher interviews, and student surveys. The research focus will cover several important aspects, including (1) The use of m-Learning in providing relevant and varied learning resources to students, (2) The effectiveness of m-Learning in increasing student motivation and involvement in project-based learning models, ( 3) The impact of m-Learning on students' collaborative skills and creativity in developing their projects, (4) Teachers' perceptions of the use of m-Learning in project-based learning models. It is hoped that the results of this research will provide a better understanding of the role of m-Learning in the context of project-based learning in elementary schools. The findings of this study can provide insight to educators, teachers, and decision-makers in the field of education to optimize the use of technology in an effort to improve the quality of learning in elementary schools.